Endoscopic neo-anastomosis by Rendez-vous technique for the treatment of complete occlusion of bilioenteric anastomoses and distal bile ducts (case series) - Steinbrück, Ingo; Otto, Helge; Ullrich, Sebastian; Ruether, Christoph; Fischbach, Roman; Pohl, Jürgen; Hagenmüller, Friedrich (Zeitschrift für Gastroenterologie, 2021)
Background and aims The complete occlusion of bilioenteric anastomoses is a rare and challenging clinical condition. Repeated surgery is burdened with technical difficulties and significant morbidity. We report the first series of completely occluded bilioenteric anastomoses resp. distal bile duct successfully treated by simultaneous percutaneous and retrograde endoscopic interventions. Patients and methods This case series includes 4 patients with obstructive jaundice and/or recurring cholangitis and pain due to complete fibrotic occlusion of a hepaticojejunostomy (3 patients) and the distal bile duct (1 patient). After performing PTCD and stepwise dilation of the biliocutaneous tract, we tried to approach the occluded anastomosis from 2 sides by simultaneous percutaneous cholangioscopy and peroral device-assisted enteroscopy/duodenoscopy. By cutting through the separating tissue layer with a needle knife under endoscopic and fluoroscopic control using diaphanoscopy, a new anastomosis should be established followed by dilation of the neoanastomosis with subsequent percutaneous transhepatic drainage for a minimum of 1 year to prevent re-occlusion. Results The Rendez-vous maneuver was successful in 3/4 cases. In one case, the retrograde access to the anastomosis failed, so the neoanastomosis was cut under cholangioscopic and fluoroscopic guidance only. The neoanastomosis could be established successfully in all 4 cases. Jaundice, cholangitis, and pain disappeared. Minor periinterventional adverse events were cholangitis (n = 1) and pneumonia (n = 1) due to aspiration, which could be managed conservatively. No serious adverse events were observed, and no re-occlusion of any neoanastomosis occurred during the follow-up before and after removal of the percutaneous drainage. Conclusion Simultaneous percutaneous cholangioscopy and device-assisted enteroscopy/duodenoscopy with endoscopic creation of a neoanastomosis is a possible concept for the treatment of completely occluded bilioenteric anastomoses and distal bile ducts. This case series confirms the feasibility, safety, and long-term effectiveness of this treatment.
Keywords: Verschluss der Gallenanastomose; biliäre Neoanastomose; PTCD; Cholangioskopie; geräteunterstützte Enteroskopie; Einzelballon-Enteroskopie